Improvements in diagnostic tools for early detection of psoriatic arthritis. (1st November 2016) - D'Angelo, Salvatore; Palazzi, Carlo; Gilio, Michele; Leccese, Pietro; Padula, Angela; Olivieri, Ignazio
ABSTRACT: Introduction : Psoriatic arthritis (PsA) is a heterogeneous chronic inflammatory disease characterized by a wide clinical spectrum. The early diagnosis of PsA is currently a challenging topic. Areas covered : The literature was extensively reviewed for studies addressing the topic area "diagnosis of psoriatic arthritis". This review will summarize improvements in diagnostic tools, especially referral to the rheumatologist, the role of patient history and clinical examination, laboratory tests, and imaging techniques in getting an early and correct diagnosis of PsA. Expert commentary : Due to the heterogeneity of its expression, PsA may be easily either overdiagnosed or underdiagnosed. A diagnosis of PsA should be taken into account every time a patient with psoriasis or a family history of psoriasis shows peripheral arthritis, especially if oligoarticular or involving the distal interphalangeal joints, enthesitis or dactylitis. Magnetic resonance imaging and ultrasonography are useful for diagnosing PsA early, particularly when isolated enthesitis or inflammatory spinal pain occur.